Ta'lim Management Through the Integration of Verses 30-35 Surah of Al-Baqarah and Hadith: a Historical and Textual Analysis - Hazaa, Zuhair Mubarrak; Tumangger, Maruli; Faisal, Ahmad; Gunawan, Indra (Journal of Islamic Education Research, 2025)
This study examines the management of ta'lim through an integrative analysis of Surah Al-Baqarah verses 30-35 and thematic hadith. The research aims to describe ta'lim as an Islamic education management concept that transcends the mere transfer of knowledge, emphasizing holistic education encompassing cognitive, moral, and character development. This study employs a literature-based thematic analysis (maudu'i) that integrates the Qur'an and Hadith as foundational sources. The findings reveal that ta'lim is an integral process in Islamic education that combines knowledge transmission with character formation, guided by divine teachings. The concept emphasizes the unity of cognitive and affective domains, forming a balanced approach to education. This research further demonstrates the relevance of ta'lim in contemporary educational contexts, particularly in formal and non-formal institutions such as pesantren and madrasah. The study's unique contribution lies in its integrative perspective, which highlights the synergy between Qur'anic verses and hadith in shaping a holistic Islamic education framework. It offers a renewed understanding of ta'lim as the foundation for comprehensive human development.